PERANCANGAN REBRANDING EVENT THE ELITE SHOWCASE 2021 PLANNING OF “THE ELITE SHOWCASE 2021” EVENT’S REBRANDING - M Fikri Akbar; Agung Eko Budiwaspada; Wegig Murwonugroho (Universitas Trisakti, 2021)
AbstractThis study discusses an organizer of a car modification exhibition, namely The Elite Production. This event organizer always tries to be a barometer of car modification in Indonesia which is held at ICE BSD, South Tangerang City. Although The Elite Production with its event has been running since 2015, this event organizer is still unable to compete with its competitors. The defeat of the competition was because The Elite Production lost in terms of branding. To be able to compete and beat its competitors, The Elite Showcase 2021 must carry out rebranding as a creative strategy to raise The Elite Showcase 2021 brand in the face of competitors. The method chosen for re-branding is to use “Design Thinking”. The stages in carrying out the design thinking method are empathize, define, ideaty, and test. Before the new branding is inaugurated, it must first go through several trials to the public, starting from several prototypes, until finally becoming a visual identity of The Elite Production 2021, which is ready to compete with its competitors in the car modification exhibition event.Keywords: event organizer, exhibition, car modification, design thinking AbstrakPenelitian ini membahas tentang sebuah penyelenggara pameran modifikasi mobil, yaitu The Elite Production. Event Organizer ini selalu berusaha menjadi barometer modifikasi mobil di Indonesia yang diadakan di ICE BSD, Kota Tangerang Selatan. Walaupun The Elite Production dengan eventnya sudah dijalankan sejak tahun 2015, tetapi event organizer ini masih kalah bersaing dengan para kompetitornya. Kekalahan persaingan tersebut karena The Elite Production kalah dari segi branding. Untuk dapat bersaing dan mengalahkan para kompetitornya, The Elite Showcase 2021 harus melakukan rebranding sebagai strategi kreatif untuk menaikkan brand The Elite Showcase 2021 dalam menghadapi kompetitor. Metode yang dipilih untuk melakukan re-branding adalah dengan menggunakan “Design Thinking”. Tahapan dalam menjalankan metode design thinking adalah emphatize, define, ideaty, dan test. Sebelum branding baru diresmikan, harus terlebih dahulu melalui beberapa uji coba ke publik, mulai dari beberapa prototype, sampai akhirnya menjadi sebuah identitas visual dari The Elite Production 2021, yang siap bersaing dengan para kompetitornya dalam ajang pameran modifikasi mobil.Kata kunci: event organizer, pameran, modifikasi mobil, design thinking